Vlog Sebagai Hasil Produk Belajar Siswa dalam Keterampilan Berbicara Bahasa Arab di MTsN Kota Batu Malang - Rahmayanti, Indah; Fitriani, Laily; Aziz, Abdul (Al Maghazi : Arabic Language in Higher Education, 2023)
In practicing Arabic speaking skills, Batu City MTsN students use a conversation/hiwar text reading system. So speaking skills have not been trained. This research methodology combines qualitative and quantitative approaches. The data collection methods used were questionnaires, interviews and observations. The research data sources were teachers and 29 students of class VIII MTsN Batu City. Analysis of data obtained from a 1-5 Likert scale questionnaire using SPSS version 26 with data tabulation. The research results show that Vlogs as a learning product for MTsN Batu City students can motivate students to learn. Students feel happy, enthusiastic and easy to learn to speak Arabic. Apart from that, students' Arabic speaking skills improved and they became more active in asking questions to the teacher. Vlogs as a product of student learning are also suitable for practice in learning Arabic speaking skills.